On the Onset Time of Several SPE/GLE Events: Indications from High-Energy Gamma-Ray and Neutron Measurements by CORONAS-F. (14th February 2013) - Kurt, Viktoria; Kudela, Karel; Yushkov, Boris; Galkin, Vladimir
Abstract : We analyzed the high-energy gamma and neutron emissions observed by the SONG instrument onboard the CORONAS-F satellite during August 25, 2001, October 28, 2003, November 4, 2003, and January 20, 2005 solar flares. These flares produced neutrons and/or protons recorded near Earth. The SONG response was consistent with detection of the pion-decay gamma emission and neutrons in these events. We supposed that a time profile of the soft X-ray derivative was a good proxy of time behavior of the flare energy release. Then we showed that time intervals of the maximum both of energy release and pion-decay-emission coincided well. We determined the onset time of GLEs 65, 69 on the basis of neutron monitor data using the superposed epoch method. The time of high-energy proton onset on November 4, 2003 was found from the GOES data. The time delay between the high-energy gamma ray observation and the high-energy protons onset time was <5 minutes. This time lag corresponds to the least possible proton propagation time. So, we conclude that in these events both protons interacted in the solar atmosphere and the first protons which arrived to Earth, belonged to one and the same population of the accelerated particles.